Bio-Adsorption of Aniline from Aqueous Solutions using Activated Raw Sludge - Mojtaba Afsharnia (Journal of Global Pharma Technology, 2017)
Aniline is a simple aromatic ring compound with wide application in several industries. Since it is soluble and highly toxic, aniline is threatening to human and environment and can disturb aqueous species life. Aniline also has mutagenic and carcinogenic properties. The aim of the present study was to eliminate aniline from aqueous solutions by the use of activated raw sludge. In this experimental study, the efficiency of activated raw sludge in eliminating aniline along with the impact of other influential variables such as pH (3, 5, 7, 9, 11), contact time (0-120 minutes), adsorbent dose (0.2, 0.4, 0.6, 0.8, 1.5 mg/L) and aniline initial concentration (10-250 mg) was investigated. Adsorption isotherm was assessed using Freundlich and Langmuir isotherms. The results indicated that the maximum efficiency of activated raw sludge in eliminating aniline was 80% which was achieved at the optimum condition of pH 11, contact time of 30 minutes, 0.2 mg/L adsorbent dose and aniline initial concentration of 200 mg/L. In addition, isotherm data showed the most fitness into Langmuir adsorption model (R2 0.990). Therefore, activated raw sludge possesses a high capacity to eliminate aniline from aqueous solutions and chemical industry wastewater.Keywords: Aniline, adsorption, sludge, adsorption, isotherms, Langmuir